Application of Grey Correlation Degree and TOPSIS Method in Evaluation of Power Quality - Fan Li-Guo; Wang Hai-Feng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Aiming at solving multi-criteria decision problems in power quality, a new decision-making method based on grey correlation degree and TOPSIS is proposed. On the basis of introducing the concept of grey correlation degree into traditional TOPSIS, a new relative similarity degree is established to decide power quality by combining Euclidean distance with grey correlation degree. Error originated from biased thinking due to subjective and objective factors in decision-making problem when using single method could be overcome by using the method and reliability of evaluation result in electric material tendering can be boosted up. Example shows that power quality could be effectively estimated by use the method and the method is an effective instruction for PQ evaluation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5251